Relationship Between Self-Efficacy and Mental Toughness With Sports Performance in Futsal Players - Mulyadi, Ahmad; Tomoliyus, Tomoliyus; Sukamti, Endang Rini; Alim, Abdul; Ulviani, Tri (International Journal Labs, 2025)
This study examines the relationship between self-efficacy and mental toughness with futsal athlete performance through a Systematic Literature Review (SLR). From 15 scientific articles analyzed, it was found that self-efficacy, a player's belief in their own abilities, plays a crucial role in improving motivation, decision-making, and persistence during matches. Meanwhile, mental toughness helps athletes manage stress, recover from failure, and maintain focus amidst the fast-paced and intense dynamics of futsal play. The interaction between the two strengthens a player's ability to perform optimally in stressful competitive situations. This study emphasizes the importance of developing psychological training programs that integrate self-efficacy and mental toughness to maximize futsal athlete performance. Furthermore, further research is needed to examine the influence of these psychological variables across different cultural contexts, genders, and levels of competition.